Requirements for Development Al-Qardabiya International Airport as a Logistics center (Economic studies journal, 2025)
This study addressed the requirements for transforming Al-Qardabiya Airport into a global logistics center in North Africa, And distinguished the best options for diversifying sources of income, Especially since Libya is located at the intersection of two main aviation axes, Horizontal in the north, extending along the northern African coast, and vertical, which passes through the middle, Including from north to south. Libya can gain an optional opportunity in aviation movement. To become a center for refueling, Transporting passengers and goods, And a destination for tourists, Due to its natural and historical assets that some African and European countries lack, In addition to its location in the middle of the African continent and its proximity to Europe. The study followed the descriptive analytical approach, and the study community consisted of all employees at Al-Qardabiya International Airport, numbering 35 male and female workers. The questionnaire form was used as a main tool in collecting field data from the study community, As the comprehensive enumeration method was followed in studying 35 questionnaires, representing 78% of the total number of distributed questionnaires. The Statistical Program for Social Sciences (SPSS) was used in analyzing the data, and the study reached many results, the most important of which are: The airport is located in an open area and there is nothing that obstructs the view. It became clear that the geographical location of the city of Sirte allows for the establishment of a global logistics center, and that logistics centers are considered one of the best options for diversifying sources of income. It also became clear that there is a lack of awareness among decision-makers of the economic and strategic importance of logistics centers, and that the design of Al-Qardabiya International Airport qualifies it to be a logistics center in North Africa. The free zone planned to be established in Sirte seaport will not be feasible unless there is an international airport in the city to serve it. The most important recommendation of the study is that it is necessary to contract with specialized international companies to transform Al-Qardabiya Airport into a global logistics center in North Africa, and to work on linking Al-Qardabiya International Airport to the free zone and Sirte seaport, to be a global logistics center in Sirte and a transit point between Africa and Europe
Keywords: Al-Qardabiya Airport; Logistics Center; Requirements; Global Port; Logistics